ANALISIS KIMIA BATANG AREN (ARENGA PINNATA MERR) DARI JASINGA, BOGOR - Gusmailina Gusmailina; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1989)
Chemical    analyses   of  Aren   stem   (Arenga  pinnata  Merr)  from  Jasinga,  Bogor  has  been  conducted   at  the  Forest Products  Research  and Development   Centre  laboratory  in Bogor.  The analyses comprised  of the determination   of cellulose, lignin,  pentosan,   ash and  silica,   calorific   value,  extractioes  and  the  solubility    in sodium   hydroxide.  These  analyses  were commonly   conducted   to determine   basic characteristics  and  ultimate   uses of  wood.The  average of  the   cellulose,    lignin,  pentosan,    ash and  silica,   extractives    content,   solubility   in  sodium   hydroxide and  calorific   value  of  the  peripheral  portion   were  consecutively   as follow:      25,02%,    33,7%,    19,55%,    1,4   and  0,51%,6,65  % (in cold water),   10,06  % (in hot  water),   3,86  % (in alcohol-benzene),    35,51  % in sodium  hydroxide   and 4406  kal/g. While  for  the  central  portion,   the  above  analyses  showed   averages as  follow   :    44,82   %, 36,8  %,   16,57  %,  4,18   % and  1,32  %,  22,88    % (in cold  water),  32, 74 % (in hot  water),  4,82   %  (in alcohol-benzene),     59,80   % in sodium  hydroxide   and 4035  kal/g.  The extractive  content    of Aren stem  ranked  high in the characteristics  and ultimate   uses of wood classification.Based  on  chemical  analyses,   such  as the  cellulose  content,   lignin, peniosan   and extractive   content,   the  Aren stem from  Jasinga,  Bogor,  appeared  to  be  a poor  materipl  for pulp  and paper  industry.